Reproducibility evaluation of soybean oligopeptides based on peptidomic analyses - YU Xiao-yi; XU Ju-cai; WU Ying; LIU Wan-shun; GUO Dan; LI Xiao-min (Shipin yu jixie)
Objective: This study aimed to analyze the peptide composition and evaluate the reproducibility of the soybean oligopeptides. Methods: High performance liquid chromatography tandem high resolution mass spectrometry was employed for peptidomic analysis of the soybean oligopeptides prepared at the same condition at different batches. Generality and individuality of the samples were also discussed based on the heat map analysis and principal component analysis （PCA）. Results: About 1 000 peptides were identified from each of the materials and most of them were short peptides. From the set analysis, 101 peptides were found of detectability from all samples, but there were also many peptides that could be only detected from part of the samples. Moreover, differences between the fifth sample and other samples were evidently observed from the principal component analysis. Conclusion: Though prepared at the same conditions, commonalities and differences coexisted across the samples from different batches. In practical production of oligopeptides, efforts should be made to narrow the differences and increase the commonalities, so that the reproducibility of the products can be improved.